2012
DOI: 10.4028/www.scientific.net/msf.727-728.746
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of YSZ-LSM Semi-Cell by Colloidal Processing

Abstract: Yttria stabilized zirconia (YSZ) is the most common electrolyte in solid oxide fuel cells (SOFC). The planar configuration is widely used for designing single cells, in which a thick cathode layer can be used as the supporting electrolyte film. The manufacture of the semi-cell formed by anode and electrolyte has been widely studied and there are many works dealing with its colloidal processing. However, the semi-cell formed by cathode and electrolyte has received much lower attention. This work deals with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The zeta potential behaviour of the commercial 8YSZ powder employed in this work has been studied in previous work [44], the isoelectric point being reported to occur at pH 5.2. In that work it was demonstrated that the addition of a polyelectrolyte shifted down the isoelectric point.…”
Section: Resultsmentioning
confidence: 99%
“…The zeta potential behaviour of the commercial 8YSZ powder employed in this work has been studied in previous work [44], the isoelectric point being reported to occur at pH 5.2. In that work it was demonstrated that the addition of a polyelectrolyte shifted down the isoelectric point.…”
Section: Resultsmentioning
confidence: 99%